Tight Binding of Plasmid DNA With Self-Assembled Tetramethylguanidinium Conjugated Polyethylenimine Suppresses Transfection Efficiency - Yadav, Santosh; Sharma, Ashwani Kumar; Kumar, Pradeep (Frontiers in Nanotechnology, 2021)
Here, we have demonstrated that on modification of linear polyethylenimine (lPEI, LP) with amphiphilic 3-bromopropyltetramethylguanidinium (PTMG) linker, the transfection efficiency exhibited by the modified polymers decreased while cell viability improved. A series of LP-PTMG polymers was synthesized by the reaction of varying amounts of 3-bromopropyl tetramethylguanidinium linker with lPEI (25 kDa). These modified polymers interacted efficiently with pDNA and formed nanosized complexes as shown by dynamic light scattering analysis. The size of the complexes in the series LP-PTMG/pDNA was observed in the range of ∼178–205 nm. The interaction of modified polymers with plasmid DNA was stronger than linear PEI as evidenced by heparin release assay which showed ∼83% pDNA release from LP-PTMG-3/pDNA complexes in comparison to ∼95% in lPEI/pDNA complexes on treatment with same amount of heparin suggesting the formation of self-assembled structures in modified polymers. The transfection studies in HeLa and Chinese hamster ovary cells showed a decrease in transfection efficiency of LP-PTMG polymers, the reason for this may be strong binding of modified polymers with pDNA due to accumulation of charge on the surface. This finding showed the significance of optimum binding of polymer and DNA to form polyplexes as well as release of DNA from the polyplexes.